QISĀS DAN HUDŪD SERTA RELEVANSINYA DENGAN HAK ASASI MANUSIA - Munadi Munadi (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2013)
in view of Islam every human being has rights that must be respected,protected and maintained, namely religion, life, property, reason and honor. Fifthrights are human rights (dharuriyat al khams) that should not be disturbed. Islamsets strict penalties against human rights violations in the form of qisas andhudud. Although a cursory view this cruel punishment, but it contains themeaning and profound wisdom, both for the offender or others. Punishment iszawajir or as a preventive efforts (prevention) to cause fear for others not to dareto commit a similar crime. The situation is very effective in enforcing the law andensuring and upholding human rights.